2015
DOI: 10.1097/ico.0000000000000541
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Role of Bacteria in the Development of Acanthamoeba Keratitis

Abstract: These results suggest that the presence of bacteria in Acanthamoeba may be required for the development of AK.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 39 publications
2
12
0
Order By: Relevance
“…In this case, coinfection of bacteria may have been one reason of the severity of AK. This particular case in the severe group was interesting because the presence of bacteria in AK was reported to be a requirement for the development of AK 24…”
Section: Discussionmentioning
confidence: 95%
“…In this case, coinfection of bacteria may have been one reason of the severity of AK. This particular case in the severe group was interesting because the presence of bacteria in AK was reported to be a requirement for the development of AK 24…”
Section: Discussionmentioning
confidence: 95%
“…The rationale for the use of antibiotics is the parasites thrive on bacteria, and phagosomes-containing bacteria have been demonstrated in the cytoplasm of the parasitic cells. [ 58 59 60 ] Similarly, there are reports on successful treatment of infection with the addition of voriconazole in patients not responding to conventional anti- Acanthamoeba treatment. [ 61 ] One can consider these additional therapies in patients not responding to conventional medical management.…”
Section: Treatmentmentioning
confidence: 99%
“…89 Nakagawa et al 89 showed that pretreatment of Acanthamoeba with levofloxacin markedly reduced disease activity, suggesting another potential, and readily available, treatment avenue.…”
Section: The Future?mentioning
confidence: 99%